How does purchasing behaviour vary between SME companies and larger companies? - Sagar, Rajesh (2012)
Background problem: Procurement has been recognised as important to small companies. However, there remains a lack of focus in the literature on procurement for SMEs and purchasing within the smaller firms themselves receives little or no attention. The literature on purchasing practices in SMEs has typically drawn from work on larger firms. Prior research has not sufficiently explored what small firms ‘do’, consequently critiquing SME practices without fully appreciating what these practices are. Models and approaches used to describe an organisation’s position and progress in procurement are focused too much on large organisations and are not sufficiently relevant to SMEs.